Back to front and upside down! - Alexander, Claire (Grand Rapids MI : Eerdmans Books for Young Readers, 2012)
While the rest of the class makes birthday cards for the principal, Stanley struggles with his words and letters.
Ages 4-7.
Schneider Family Award for Young Children, 2013
Keywords: Dyslexia -- Fiction; Schools -- Fiction; Animals -- Fiction; Dyslexia -- Juvenile fiction; Schools -- Juvenile fiction; Animals -- Juvenile fiction; Picture books for children